2021
DOI: 10.2147/ijgm.s328914
|View full text |Cite
|
Sign up to set email alerts
|

Patients, Prescribers, and Institutional Factors Associated with Inappropriate Use of Acid Suppressive Therapy in Medical Wards: An Experience of a Single-Center in Saudi Arabia

Abstract: Purpose: To identify factors associated with inappropriate acid-suppressive therapy (AST) use in hospitalized medical ward patients. Patients and Methods: This was a combined retrospective cohort study reviewing the electronic medical records of medical ward in a secondary university hospital between January 2018 and July 2019, in addition to prescriber surveys about AST knowledge. We included adult patients (≥18 years old) admitted to the medical ward who received at least one dose of AST during their hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…risk medications had higher odds of being prescribed AST inappropriately. 24 This finding reflects the practitioner’s behavior in prescribing PPIs to most patients upon admission and discharge rather than not prescribing them because PPIs are well-known drugs with reasonable safety profiles and few complications, making prescribers less hesitant to order and prescribe them. Many reports have shown that PPIs are associated with long-term complications such as osteoporosis, which increases the risk of C. difficile infection.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…risk medications had higher odds of being prescribed AST inappropriately. 24 This finding reflects the practitioner’s behavior in prescribing PPIs to most patients upon admission and discharge rather than not prescribing them because PPIs are well-known drugs with reasonable safety profiles and few complications, making prescribers less hesitant to order and prescribe them. Many reports have shown that PPIs are associated with long-term complications such as osteoporosis, which increases the risk of C. difficile infection.…”
Section: Discussionmentioning
confidence: 91%
“…26 Other studies conducted in Saudi Arabia, Portugal, and Shanghai found higher rates of inappropriate use; 76.4%, 61.5%, and 47%, respectively. 24 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In another study, it was determined that 63% of the doctors who prescribe PPIs were internal medicine specialists. 12 Since the pharmacy where our study was conducted was located just across from the family health center, we think that the prescriptions containing PPIs in our study were mostly written by family physicians.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, this rate was determined as 11% for omeprazole. 12 A study conducted in Ireland found that the most commonly prescribed PPIs in the hospital was esomeprazole (54%). 14 In a study conducted in Italy, the most commonly prescribed PPIs drug was found to be omeprazole.…”
Section: Figure 1bmentioning
confidence: 99%